2017
DOI: 10.3906/sag-1605-7
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish version of the Physical Activity Scale for theElderly (PASE): its cultural adaptation, validation, and reliability

Abstract: Background/aim: This study aimed to describe the cultural adaptation of the Turkish Physical Activity Scale for the Elderly (PASE) and to examine the reliability and validity of the scale in older Turkish adults.Materials and methods: Eighty elderly people were recruited for the study. The assessments included the PASE, the International Physical Activity Questionnaire (IPAQ), the Short Physical Performance Battery and Short Form-36 Quality of Life Questionnaire (SF-36), and the Mini Mental State Test. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
60
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 24 publications
10
60
2
1
Order By: Relevance
“…Examining the mean PASE score showed that 32.6% of the elderly led a sedentary lifestyle, while 39.7% performed moderate and strenuous physical activities. Unlike the current study, Ayvat et al found a mean PASE score indicating moderate physical activity . Other studies in the literature have also that reported mean PASE scores indicating moderate physical activity .…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Examining the mean PASE score showed that 32.6% of the elderly led a sedentary lifestyle, while 39.7% performed moderate and strenuous physical activities. Unlike the current study, Ayvat et al found a mean PASE score indicating moderate physical activity . Other studies in the literature have also that reported mean PASE scores indicating moderate physical activity .…”
Section: Discussioncontrasting
confidence: 83%
“…Unlike the current study, Ayvat et al found a mean PASE score indicating moderate physical activity . Other studies in the literature have also that reported mean PASE scores indicating moderate physical activity . In their study, Curcio et al determined that 32.1% of the elderly led a sedentary lifestyle, while 37.2% performed light physical activities, and 30.7% performed moderate physical activities .…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations